Application of Design Thinking Method in Designing the User Interface Prototype for the Website of the Informatics Engineering Study Program at Dian Nuswantoro University - Mahardika, Pramesthi Qisthia Hanum; Luthfiarta, Ardytha (Journal La Multiapp, 2024)
In today's era, with the rapid development of technology such as the internet, human work can be significantly aided. This advancement positively impacts the education sector in terms of teaching, learning, and information dissemination. This development increases the use of websites, making the user interface an essential aspect of user comfort. The website of the Informatics Engineering study program at Dian Nuswantoro University has some deficiencies in its user interface. Therefore, the researcher has designed a user interface prototype to facilitate user interaction with the website, using the design thinking method. The designed user interface prototype is expected to address existing problems, meet user needs, and enhance campus services.